TANGGUNG JAWAB KELUARGA DALAM PENDIDIKAN ANAK - Syahraeni, Andi (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2015)
In an effort to produce the next generation of robust and high quality, necessary for consistent effort and continuous of the parents in carrying out the task of preserving, nurturing and educating their children both physically and spiritually until the child is an adult and / or capable of standing alone, where the task This is the duty of parents. maintenance issues and parenting is a matter which concerns the protection of the welfare of the children themselves in an effort to improve the quality of children on growth and prevent neglect and unfair treatment to realize the child as a whole person, tough, intelligent and virtuous, the shelter for a child are the parents. in the lives of people everywhere, the family is the smallest unit whose role is very great. A very large role was caused, because the family has a very important function in the survival of society. Process know the rules and the values espoused, for the first time obtained in the family.